Penggunaan Aplikasi Laksa dalam Mewujudkan Tranparansi dan Partisipasi Masyarakat di Kota Tangerang - Muhammad Rizki; Haniah Hanafie (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study discusses the use of the LAKSA application as a forum for the aspirations of the people of Tangerang City in realizing the principles of transparency and participation. The problem of transparency and participation in public services in Tangerang City has not gone well even though as an industrial city, the community's need for public services is quite high. The purpose of this study was to analyze the role of the LAKSA application in creating transparency and participation in the Tangerang City government, as well as to find out the supporting and inhibiting factors for using the LAKSA application. This research was conducted using qualitative analysis methods, with data collection techniques through interviews, documentation, and observation. The theory used is transparency put forward by Agus Dwiyanto and public participation theory by Arnstein, used as a data analysis technique. The results of research using this theory show that in terms of service transparency such as disclosure of information on costs, time, and requirements for using the LAKSA application, it works quite well. The convenience of users in using the application is fairly good. In creating participation, it can be concluded that the LAKSA application is effective in growing people's wishes in conveying aspirations. Participation that is created in the use of the LAKSA application is control by residents.